2002
DOI: 10.1152/ajpendo.00457.2001
|View full text |Cite
|
Sign up to set email alerts
|

Role of PKC isoforms in glucose transport in 3T3-L1 adipocytes: insignificance of atypical PKC

Abstract: To elucidate the involvement of protein kinase C (PKC) isoforms in insulin-induced and phorbol ester-induced glucose transport, we expressed several PKC isoforms, conventional PKC-alpha, novel PKC-delta, and atypical PKC isoforms of PKC-lambda and PKC-zeta, and their mutants in 3T3-L1 adipocytes using an adenovirus-mediated gene transduction system. Endogenous expression and the activities of PKC-alpha and PKC-lambda/zeta, but not of PKC-delta, were detected in 3T3-L1 adipocytes. Overexpression of each wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 45 publications
(37 reference statements)
4
27
1
Order By: Relevance
“…Insulin was shown to activate PKC-␣ and, to a lesser extent, PKC-␤ and PKC-/ in 3T3-L1 adipocytes (29,30) and PKC-/ in rat adipocytes (37). However, PKC-␣ and PKC-activation by insulin has not been observed in all studies (51,52). In this study, insulin was found to affect the subcellular distribution of PKC-␣ and PKC-/, whereas it did not influence translocation or tyrosine phosphorylation of PKC-␤.…”
Section: Discussionmentioning
confidence: 95%
“…Insulin was shown to activate PKC-␣ and, to a lesser extent, PKC-␤ and PKC-/ in 3T3-L1 adipocytes (29,30) and PKC-/ in rat adipocytes (37). However, PKC-␣ and PKC-activation by insulin has not been observed in all studies (51,52). In this study, insulin was found to affect the subcellular distribution of PKC-␣ and PKC-/, whereas it did not influence translocation or tyrosine phosphorylation of PKC-␤.…”
Section: Discussionmentioning
confidence: 95%
“…The phosphorylation and activation of PKC λ/ζ are stimulated by insulin [75,76] and the expression of constitutively active PKC λ/ζ mutants reportedly increases whereas dominantinterfering mutants and microinjection of blocking antibodies inhibit insulin-induced GLUT4 translocation [70][71][72]. However, other studies found no evidence of direct involvement of PKC λ/ζ in this process [77]. Despite PKC λ/ζ not possessing a PH domain, these enzymes are recruited to the plasma membrane, and are activated by PDK-1-dependent phosphorylation in response to insulin stimulation [78,79].…”
Section: (2) Downstream Effectors Of the Pi 3-kinase Signaling Pamentioning
confidence: 96%
“…These include the following: (1) overexpression of wild-type and dominant interfering PKC mutants [e.g. PKCζ as a regulator of RelA transcriptional activity (Anrather et al, 1999); PKCα and PKCδ as regulators of glucose transport (Tsuru et al, 2002); PKCα and PKCθ as regulators of calcineurin-induced transactivation (Ishaq et al, 2002); (for a review, see Dempsey et al, 2000)]; (2) interference with PKC expression using ribozymes [e.g. PKCα as a regulator of glioma cell growth (Sioud and Sorensen, 1998)]; (3) interference with expression using antisense oligonucleotides [for reviews of the literature with an emphasis on therapeutically relevant approaches see (Tamm et al, 2001;Goekjian and Jirousek, 2001;Swannie and Kaye, 2002)]; and (4) interference with PKC function using peptides that induce or block PKC interactions with targeting proteins (for reviews, see Csukai and Mochly-Rosen, 1999;Jaken and Parker, 2000).…”
Section: Pkcs As Paradigmatic C1-domain-containing Dag Receptorsmentioning
confidence: 99%